2021
DOI: 10.3389/fnbeh.2021.633005
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychobiological Fingerprints of Chronic Fatigue in Sarcoidosis

Abstract: BackgroundChronic fatigue is a prominent symptom in many sarcoidosis patients, affecting quality of life and interfering with treatment. This study investigated neuropsychobiological mechanisms and markers of chronic fatigue in sarcoidosis.MethodsThirty patients with a histological diagnosis of sarcoidosis were included. The Multidimensional Fatigue Inventory was used to define patients with and without chronic fatigue. All patients were then characterised using several depression, quality of life questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Interestingly, the study by Harper et al showed a significantly lower P level in the white matter of patients with major depressive disorder compared to healthy controls, and a significant negative correlation between the P level and the symptoms' intensity, which is explained by altered bioenergetic metabolites turnover [31]. Kattenbach et al found altered brain activation in patients with chronic fatigue [32]. Altogether, those findings may support the role of P in fatigue pathophysiology.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the study by Harper et al showed a significantly lower P level in the white matter of patients with major depressive disorder compared to healthy controls, and a significant negative correlation between the P level and the symptoms' intensity, which is explained by altered bioenergetic metabolites turnover [31]. Kattenbach et al found altered brain activation in patients with chronic fatigue [32]. Altogether, those findings may support the role of P in fatigue pathophysiology.…”
Section: Discussionmentioning
confidence: 93%